Psychological Need Satisfaction And Employee Outcomes: A Self-Determination Theory Perspective - Nur Qamarina Sharom; Intan Fatimah Anwar; Sumaiyah Abd Aziz; Umi Hamidaton Mohd Soffian Lee (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA